Sense and no(n)-sense of energy security indicators - Christoph Böhringer; Markus Bortolamedi (University of Oldenburg, Department of Economics, 2015)
Energy security ranks high on the policy agenda of many countries. To improve on energy security, governments undertake regulatory measures for promoting renewable energy, increasing energy efficiency, or curbing carbon dioxide emissions. The impacts of such measures on energy security are typically monitored by means of so-called energy security indicators. In this paper, we show that the common use of wide-spread energy security indicators falls short of providing a meaningful metric. Regulatory measures to improve on energy security trigger ambiguous effects across energy security indicators. We conclude that a major pitfall of energy security indicators is the lack of a rigorous microeconomic foundation.
Keywords: D58; Q48; 330; energy security; energy security indicators; computable general equilibrium analysis